Peningkatan Keaktifan dan Hasil Belajar Pelajaran Komputer Jaringan Dasar Menggunakan Model Pembelajaran Problem Based Learning - Retno Christyo Ekowati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The level of activity and learning outcomes of students in Basic Network Computer learning for class X TKJ SMK Negeri 1 Pleret has not been as expected. This study aims to determine the increase in the activity and learning outcomes of Computers and Basic Networks through problem-based learning models which include psychomotor aspects or skills, cognitive or knowledge, and affective or attitude aspects. Class action research will be carried out in two cycles where each cycle consists of four stages, namely planning, action, observation and reflection. The subjects of this study were students of class X TKJ especially class X TKJ A for the 2019-2020 academic year which consisted of 37 students, consisting of 33 boys and 4 girls. Data collection techniques were carried out using written tests and observations, as well as analysis of quantitative and qualitative descriptive data. The results of this class action research showed that the learning outcomes of students in pre-cycle obtained a complete percentage of 40.5%, cycle I obtained a complete percentage of 43.24%, and in cycle II obtained a complete percentage of 81.08%. Increased activity and learning outcomes are indicated by an increase in the percentage of pre-cycle completeness to cycle I by 6.7% and from cycle I to cycle II an increase in the percentage of completeness by 87.5% Based on research results show that learning with the problem based learning model can increase activity and results learn computer network basic learners.